Fluorine doped tin oxide as an alternative of indium tin oxide for bottom electrode of semi-transparent organic photovoltaic devices - Amirah Way; Joel Luke; Alex D. Evans; Zhe Li; Ji-Seon Kim; James R. Durrant; Harrison Ka Hin Lee; Wing C. Tsoi (AIP Advances, 2019)
Indium tin oxide (ITO) is commonly used as the transparent bottom electrode for organic solar cells. However, it is known that the cost of the ITO is quite high due to the indium element, and in some studies ITO coated glass substrate is found to be the most expensive component of device fabrication. Moreover, indium migration from ITO can cause stability issues in organic solar cells. Nevertheless, the use of ITO as the bottom electrode is still dominating in the field. Here, we explore the possibility of using fluorine doped tin oxide (FTO) as an alternative to ITO for the bottom electrode of organic solar cells particularly on semi-transparent cells. We present side-by-side comparisons on their optical, morphological and device properties and suggest that FTO could be more suitable than ITO as the bottom electrode for glass substrate based organic photovoltaic devices.